2021
DOI: 10.3389/fcimb.2021.617481
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Gram-Negative Bacteria Pseudomonas aeruginosa Influences the Lung Dendritic Cell Population Signature by Interfering With CD103 Expression

Abstract: Lung dendritic cells (DCs) are divided into two major populations, which include CD103+XCR1+ cDC1s and CD11b+Sirpα+ cDC2s. The maintenance of their relative proportions is dynamic and lung inflammation, such as caused by exposure to lipopolysaccharide (LPS), a component of the outer membrane of Gram-negative bacteria, can have a significant impact on the local cDC signature. Alterations in the lung cDC signature could modify the capacity of the immune system to respond to various pathogens. We consequently aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Such endotoxin-based assessment of the burden of Gram-negative organisms such as Pseudomonas as well as high endotoxin levels may be significant in the assessment of machine workers’ risk of occupational lung disease. In this context, several studies have associated lung inflammatory response in machine workers with exposure to microbial endotoxins and antigens in the machining fluid [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Initial studies on the etiology of hypersensitivity pneumonitis (HP) in machinists implicated Pseudomonas as the etiological agent [ 67 ], and later studies from our laboratory have shown exacerbating effects of Pseudomonas in MWF mycobacteria-induced HP-like pathology in mice (unpublished).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such endotoxin-based assessment of the burden of Gram-negative organisms such as Pseudomonas as well as high endotoxin levels may be significant in the assessment of machine workers’ risk of occupational lung disease. In this context, several studies have associated lung inflammatory response in machine workers with exposure to microbial endotoxins and antigens in the machining fluid [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Initial studies on the etiology of hypersensitivity pneumonitis (HP) in machinists implicated Pseudomonas as the etiological agent [ 67 ], and later studies from our laboratory have shown exacerbating effects of Pseudomonas in MWF mycobacteria-induced HP-like pathology in mice (unpublished).…”
Section: Resultsmentioning
confidence: 99%
“…SDA meant for the growth of fungi did not yield any fungal colonies from the first three DCR samples (before dump, neat, and non-circulated) and SS#1. However, fungal population was detected in the subsequent samples except SS#6, 7, 12,13,14,17,18,21,23,24,28,29,31,33,34, and 37 at levels varying from 1 to 3.25 × 10 3 cfu/mL. The typical fungal colonies were identified as N. haematococca based on ITS sequencing.…”
Section: Targeted Community Profile Selective Culturing and Dna Seque...mentioning
confidence: 96%
See 1 more Smart Citation
“…Limited work has investigated the roles of DCs in chronic P. aeruginosa infection, but they are known to be activated and express co-stimulatory molecules CD80 and CD86 in the lung and regional lymph nodes in response to P. aeruginosa ( 210 ). Furthermore, P. aeruginosa appears able to modulate DC subpopulations, resulting in a skewing of the resting conventional DC (cDC) population toward cDC2s that support a Th2 response rather than cDC1s that promote Th1 and bacterial clearance ( 211 ). This fits into the existing paradigm of Th2-skewed immunity in chronic P. aeruginosa and suggests that DCs may be contributing to this later T cell imbalance.…”
Section: Immune Response To Infectionmentioning
confidence: 99%
“…This may stem in part from the current lack of knowledge on the impact of lung cancer on local DC populations, which are crucial in anticancer immunity. Previous studies by our group suggested that various inflammatory contexts profoundly impact the local DC signature, as well as disease progression [ 8 , 9 , 19 ]. Specifically, we demonstrated that the proportions of CD103 + DC1s are drastically reduced under inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%